2019
DOI: 10.3390/ma12172789
|View full text |Cite
|
Sign up to set email alerts
|

TiN-Nanoparticulate-Reinforced ZrO2 for Electrical Discharge Machining

Abstract: This study presents a fabrication route for an electrically conductive ZrO2–TiN ceramic nanocomposite with a nanoscale TiN phase occupying ≤30 vol% to improve the mechanical reinforcement of the zirconia matrix, and at the same time provide electrical conductivity to facilitate electro-discharge machining (EDM). The TiN nanoparticles were incorporated into a 3 mol% yttria-stabilized tetragonal zirconia (Y-TZP) powder, either by admixing a TiN nanopowder (MCP) or by using in-situ synthesis (ISS) via the forced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…A copper of 1 mm in diameter was selected as the tool and die steel was selected as the workpiece. The working liquid was kerosene, and the positive polarity was applied (Lazar et al , 2019). The workpiece surface needs to be polished to remove its oxide layer before the experiment, as shown in Figure 19(b).…”
Section: Materials Removal Experiments and Analysis In Single-pulse Dischargementioning
confidence: 99%
“…A copper of 1 mm in diameter was selected as the tool and die steel was selected as the workpiece. The working liquid was kerosene, and the positive polarity was applied (Lazar et al , 2019). The workpiece surface needs to be polished to remove its oxide layer before the experiment, as shown in Figure 19(b).…”
Section: Materials Removal Experiments and Analysis In Single-pulse Dischargementioning
confidence: 99%
“…They found that the relative density and Vickers hardness of the samples were improved when TiN was used as a sintering additive. Titanium nitride (TiN) demonstrated outstanding mechanical properties, such as high hardness, excellent chemical stability, and a high melting point [ 8 , 9 ]. Additionally, ZrN and TiN crystallize in the face-centered cubic (fcc) structure, resulting in the formation of solid solutions during the sintering process [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Composite materials are expected to overcome the inherent shortcomings of single-phase ceramics and bring about an overall improvement in structure and functional characteristics [9][10][11] . For example, Al2O3-ZrO2 system [12] is one of the most studied and promising ceramic composites.…”
mentioning
confidence: 99%